Constitutional Responsibility of the State for the Protection of the Right to Health in the Implementation of the Free Nutritious Meal Program - Putra, Adi (International Asia Of Law and Money Laundering (IAML), 2025)
This study focuses on the constitutional responsibility of the state for the protection of the right to health in the implementation of the free nutritious food (MBG) Program, by placing mass poisoning events as problematic indicators of the fulfillment of state obligations on children's health rights. The research uses normative juridical methods with constitutional and conceptual approaches, analyzing the obligations of the state based on the 1945 Indonesian constitution, international legal instruments, and legislation related to health and food. The findings show that there is a normative gap between the constitutional guarantee of the right to health and the weak mechanism for implementing social programs in the aspects of supervision, accountability, and legal protection. The state has not fully fulfilled the three dimensions of the constitutional obligation (obligation to respect, protect, and fulfill) in ensuring the food security of the MBG program. The weakness of technical regulations, the fragmentation of supervisory institutions, and the absence of clear accountability mechanisms reflect a disregard for the principles of the welfare state as mandated by the Constitution. This article recommends the reconstruction of a legal framework that integrates the constitutional dimension of the right to health with the operational design of the program, the institutional strengthening of integrated supervision, as well as the affirmation of state accountability mechanisms through administrative, civil and criminal channels. The fulfillment of the constitutional rights of citizens cannot be left solely to market mechanisms or returned to the logic of administrative efficiency, but must be guaranteed through a solid legal infrastructure and an effective accountability system.